EFEKTIVITAS METODE MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR MENULIS TEKS FANTASI - Emi Rosmiati; Ika Mustika (IKIP Siliwangi, 2020)
This research was motivated by the low student learning outcomes in writing fantasy texts and the effectiveness of the mind mapping method in learning to write fantasy texts. This is a problem that will be researched so that the formulation of the problem in the study is whether there are differences in student learning outcomes before and after using the mind mapping method? This study aims to determine the ability to write fantasy texts before and after using the mind mapping method. The research method used was pre-experiment in the form of one group pretest and posttest design. This research was conducted at SMP Negeri 3 Parongpong with the selected sample, namely VII A as the experimental class. The results of this study indicate a significant difference seen from the average posttest score after treatment is higher than the pretest results. Based on these results, it can be concluded that the mind mapping method is effectively used in learning to write fantasy texts in accordance with the identification of the structure and linguistic aspects.